Juridical Review of the Use of the Voting Rights of Persons with Disabilities and the Elderly according to Law Number 7 of 2017 concerning General Elections - Haura Salsabilla (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
Indonesia is a legal state that implements a democratic system, with general elections as a means of popular sovereignty. People with disabilities and the elderly have the same political rights as the rest of society and should participate in elections to elect their representatives and influence the political direction of the nation. However, there are still many obstacles that stand in their way such as hard-to-reach polling station locations, physical deficiencies, and lack of accessibility facilities. It is important to pay special attention to the participation of people with disabilities and the elderly due to their significant numbers. Efforts are needed to improve disability-friendly and elderly-friendly facilities in elections so that they can exercise their voting rights easily and comfortably. The active participation of all citizens, including persons with disabilities and the elderly, is key in realizing democratic and inclusive elections.